Synthesis and In Vitro Antimicrobial Evaluation of New Quinolone Based 2-Arylamino Pyrimidines. (16th March 2023) - Alla, Krishna; Vijayakumar, V.; Sarveswari, S.
Abstract: An efficient synthesis of new 4-hydroxy-3-(6-aryl-2-(arylamino) pyrimidin-4-yl) quinolin-2(1 H )-ones 5a–j, 6a–j, and the evaluation of their antimicrobial activity have been described. Potent antibacterial activity was shown by 6a, 5e, 5f, 6h, 6i, 5j against the testes pathogenic bacteria. Also significant antifungal activity was shown by 6b, 6d, 5e toward selective fungal strains.